Ответы и объяснения

  • jip
  • новичок
2013-04-10T16:19:23+04:00

предпологаю что 

у=(6-3)*sgrt(x)тогда

у"=-3*sgtr(x0+(6-3)/(2*sgrt(x))=0

-6*+6-3=0

y=2/3точка максимума

Лучший Ответ!
2013-04-10T16:38:57+04:00

f(x)=(6-3x)\sqrt{x}\\ f'(x)=((6-3x)\sqrt{x})'=(6-3x)'\sqrt{x}+(6-3x)*(\sqrt{x})'=\\ =-3\sqrt{x}+(6-3x)*\frac{1}{2\sqrt{x}} = -3\sqrt{x}+\frac{3}{\sqrt{x}}-\frac{3x}{2\sqrt{x}}\\ -3\sqrt{x}+\frac{3}{\sqrt{x}}-\frac{3x}{2\sqrt{x}}=0 \ | *\sqrt{x}\\ -3x+3-1,5x=0\\ -4,5x+3=0\\ -4,5x=-3\\ x=3:4,5\\ x=\frac{2}{3}

Критическая точка = 2/3

Смотри рисунок:

х(max) = 2/3 - точка максимума.

Ф-ция возростает на отрезку (-∞; 2/3);   убивает на  отрезке (2/3; +∞)